1985
DOI: 10.1172/jci112248
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of human serum immunoglobulin in immunodeficient patients with viral gastroenteritis. A pharmacokinetic and functional analysis.

Abstract: We examined the pharmacokinetics and immunological activity of human serum immunoglobulins (HSG) possessing anti-rotavirus activity which were orally administered to three children with primary immunodeficiency syndromes and prolonged gastrointestinal excretion of rotavirus. Detailed analysis of the excretion of immunoglobulins labeled with biotin or I"25 revealed that -50% of the recovered radioactivity was excreted in the stools over a 3-d period. Approximately half of the excreted radioactivity recovered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 18 publications
2
69
1
Order By: Relevance
“…Additionally, there were no subjects with treatment-emergent serious AEs and only eight subjects discontinued the study due to AEs. These findings are in agreement with previous reports examining oral immunoglobulin in neonates (Barnes et al 1982) and children or adults with serious intestinal infections (Borowitz and Saulsbury 1991;Guarino et al 1994;Losonsky et al 1985;Tacket et al 1988;1992;Tjellstrom et al 1993Tjellstrom et al , 1997.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, there were no subjects with treatment-emergent serious AEs and only eight subjects discontinued the study due to AEs. These findings are in agreement with previous reports examining oral immunoglobulin in neonates (Barnes et al 1982) and children or adults with serious intestinal infections (Borowitz and Saulsbury 1991;Guarino et al 1994;Losonsky et al 1985;Tacket et al 1988;1992;Tjellstrom et al 1993Tjellstrom et al , 1997.…”
Section: Discussionsupporting
confidence: 93%
“…We can reasonably assume that the immunoglobulin was reaching the intestinal mucosa, as immunoglobulin has been shown to remain intact when administered orally Losonsky et al 1985;Tacket et al 1988). Thus, if the hypotheses were correct, we expected to see indications of a dose-response effect, even if the IgG survival rates were low.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In clinical trials the oral administration of several different immunoglobulin preparations has revealed that it can survive passage through the gastrointestinal tract of bone marrow transplantation recipients 5 and has protective effects against infectious diarrhoea and necrotizing enterocolitis. [6][7][8][9] It may be anticipated that production and function of IgA in the gastro-intestinal tract is disrupted by the preparative regimen preceding BMT. The aim of this placebo-controlled, randomised trial was therefore to investigate whether the oral administration of an IgA-IgG preparation made from human serum would reduce gastro-intestinal toxicity or infectious complications related to autologous BMT.…”
mentioning
confidence: 99%